Comparison of the safety and efficacy of fingolimod and tofacitinib in the zebrafish model of colitis. (December 2022) - Mousavi, Taraneh; Hassani, Shokoufeh; Baeeri, Maryam; Rahimifard, Mahban; Vakhshiteh, Faezeh; Gholami, Mahdi; Ghafour-Broujerdi, Elmira; Abdollahi, Mohammad
Abstract: Background: Oral targeted small molecules, including sphingosine 1 phosphate receptor (S1PR) modulators and tyrosine kinase inhibitors (TKIs), seem to revolutionize the management of inflammatory bowel disease (IBD). To select the most effective treatment, there is an unmet need to comparatively study their mechanism of action, efficacy, and toxicity in the preclinical stage and further translate it into clinical practice. Methods: Using 2, 4, 6-trinitrobenzene sulfonic acid (TNBS)-induced adult zebrafish colitis model, LC50 of fingolimod and tofacitinib were determined based on the acute toxicity test to compare aquatic toxicity potential. Subsequently, the efficacy of different concentrations of tofacitinib and fingolimod was compared using flow cytometry, qPCR, and histopathology analyses. Results: TNBS significantly reduced the length of villi, and the number of goblet cells increased the level of TNF-α, MyD88, and NF-κB2, the thickness of villi and necrosis, and induced histopathological changes. All of these parameters were reversed almost dose-dependently with both medications, with the highest concentration of fingolimod being superior to other groups. Additionally, results from qPCR analysis suggested that these medications might suppress canonical and non-canonical NF-κB pathways by targeting toll-like receptors and MyD88. LC50 of tofacitinib and fingolimod was 0.9014 and 0.36 mg/L, respectively. Hence, both are in the cory 1 of the Global Harmonization System (GHS) aquatic toxicity and are toxic to adult zebrafish life. Conclusion: Given the better efficacy of fingolimod, it is worth translating the effectiveness and safety of S1PR modulators into IBD patients and comparing them with TKIs in head-to-head studies; albeit, their toxicity should not be overlooked. Graphical abstract: Image 1 Article Highlights: Oral-targeted small molecules have attracted tremendous attention in managing moderate-to-severe IBD, but there is insufficient data for their mechanism of action, efficacy, and ecotoxicity. Taking advantage of rapid modeling, low cost, and high structural/genetic similarities of adult zebrafish to humans, for the first time, a procedure for comparing the efficacy and aquatic toxicity of two medications (i.e., fingolimod and tofacitinib) was introduced in TNBS-induced adult zebrafish colitis model. Flow cytometry, qPCR, and qualitative and quantitative histopathology analyses were all evident of successful induction of colitis, which was enhanced almost dose-dependently with both medications, wherein the highest fingolimod concentration showed the best results compared to other groups. LC50 of tofacitinib and fingolimod was determined to be 0.9014 and 0.36 mg/L in adult zebrafish, respectively. Hence, both are in category 1 of the Global Harmonization System (GHS) aquatic toxicity and are toxic to adult zebrafish life.